UMA ROSA PARA MEUS CABELOS CRESPOS: experiência estética e política da imagem - PAIXÃO, Marli Madalena Estrela (2008)
This scientific paper is based on an ethnographic research developed in Afro Zíndze Beauty Salon, located in Historical Center in Sao Luís-Ma. This paper tries to understand symbolic, cultural, political and religious representations concerned to black men and women s hair. This research emphasizes that individual aesthetics has a relation to an image politics that is inside an identity resistence context. In this sense, hair study acquires several meanings when is related to racial relation system. Therefore, hair study can help us to think about different aspects belong to black identity. Afro Zíndze Beauty Salon is an exceptional place to this kind of investigation. In general, the curly hair even stigmatized, it has a resignification which is transformed in identity and self-esteem symbol.